Review of the literature on the topic of censorship and self-censorship in journalism in the context of freedom of speech (Herald of Journalism, 2022)
For the development of a democratic state, public understanding of freedom of speech is very important (Çarkoğlu & Andı, 2020). Journalism, which should provide impartial, objective and truthful information, is not always able to fully fulfill its role. It depends on various factors in the country and the society in which the media exists.The main purpose of the study is to determine what studies have been conducted on the topic of censorship and self-censorship in the field of media and communication and what were their main ideas; the article also seeks answers to questions such as their current relevance and importance in the information production process. Since these terms are more studied in the western world than in the post-soviet countries, this paper focuses on the work of such researchers as O'Higgins, Sen, Cook and Heilman. Kazakhstani materials on freedom of speech will also be considered.The scientific and practical significance of the work lies in the fact that the future specialist will be able to distinguish these terms from his student days in order to understand the impact of censorship and self-censorship on the formation of the media agenda and the implementation of journalistic activities.According to the study, many researchers say, that censorship is pressure from the state, and self-censorship is a response to this pressure. According to Olga Zeveleva, censorship is activated when self-censorship does not work (Zeveleva, 2020). That is, censorship is described as the result of effective work. By studying the review of western literature written in recent years, future professionals will be able to apply this knowledge for further research, understanding of media theory and journalism.Keywords: censorship, self-censorship, freedom of speech, agenda setting.